2007
DOI: 10.1007/s00015-007-1230-4
|View full text |Cite
|
Sign up to set email alerts
|

Astronomical time scale for the Middle Oxfordian to Late Kimmeridgian in the Swiss and French Jura Mountains

Abstract: Detailed investigation of facies and sedimentary structures reveals that, during the Middle Oxfordian to Late Kimmeridgian, the shallow carbonate platform of the Swiss and French Jura Mountains recorded high-frequency sea-level fluctuations quite faithfully. The cyclostratigraphic analysis within the established biostratigraphic and sequence-chronostratigraphic framework implies that the resulting hierarchically stacked depositional sequences formed in tune with the orbital cycles of precession (20 kyr) and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Magnetostratigraphy was helpful only in the Bajocian through Tithonian interval (with a hiatus at CallovianOxfordian transition) where the low-amplitude seafloor magnetic anomalies (from Ocean Drilling Program site 801 on the older part of eastern Pacific Plate) could be tied to magnetostratigraphy. The attempts to astronomically fine-tune discrete intervals of the Jurassic (see, e.g., Strasser, 2007, and a summary by Huang in Ogg and Hinnov, 2012) may help with duration of some zonal intervals, but such piecemeal efforts do not alleviate the precision issues of all of the stage boundaries that are exacerbated by the lack of reproducible radiometric control for much of the Middle and Late Jurassic. This implies that, in general, the time scale of the Jurassic and precision of the ages of many biostratigraphic zonal boundaries still remain less than well constrained.…”
Section: Jurassic Time Scalementioning
confidence: 99%
“…Magnetostratigraphy was helpful only in the Bajocian through Tithonian interval (with a hiatus at CallovianOxfordian transition) where the low-amplitude seafloor magnetic anomalies (from Ocean Drilling Program site 801 on the older part of eastern Pacific Plate) could be tied to magnetostratigraphy. The attempts to astronomically fine-tune discrete intervals of the Jurassic (see, e.g., Strasser, 2007, and a summary by Huang in Ogg and Hinnov, 2012) may help with duration of some zonal intervals, but such piecemeal efforts do not alleviate the precision issues of all of the stage boundaries that are exacerbated by the lack of reproducible radiometric control for much of the Middle and Late Jurassic. This implies that, in general, the time scale of the Jurassic and precision of the ages of many biostratigraphic zonal boundaries still remain less than well constrained.…”
Section: Jurassic Time Scalementioning
confidence: 99%
“…High-frequency sequences in Kimmeridgian to Berriasian carbonates of the Jura platform probably originated from orbitally forced sea-level changes (Colombié and Strasser, 2005;Rameil, 2005;Colombié and Rameil, 2007;Strasser, 2007). Medium-scale and small-scale sequences would thus represent the long and the short eccentricity cycle of Earth's orbit (400 ka and 100 ka) respectively.…”
Section: Relation Of Dolomitization To Orbitally Controlled Sea-levelmentioning
confidence: 99%
“…Towards the top of these sequences, higher energy deposits indicate shallowing towards the following bounding surface (e. g., small-scale sequences 3 and 4 at Péry-Reuchenette). Through their stacking pattern and within the given bio-chronostratigraphic framework it can be shown that these small-scale sequences formed in tune with the orbital short eccentricity cycle of 100 kyr (Colombié 2002;Strasser 2007). The basinal sections of Crussol and Châteauneuf-d'Oze are dominated by limestone-marl alternations.…”
mentioning
confidence: 94%